Psychophysiological parameters of qualified athletes, players and biathlonists - Lutkova N.V.; Makarov Yu.M.; Lutkov V.F.; Egorenko L.A. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to determine the dominant parameters of the psychophysiological state (PPS) in qualified athletes specializing in “sports games and biathlon”. Methods and structure of the study. Vibraimage technology was used with the VibraMed10 program. The objects of the study were highly qualified athletes (candidates for master of sports and masters of sports), specializing in “sports games” (handball, football, rugby) and specializing in “biathlon”, who are part of the national teams of St. Petersburg. A total of 28 athletes, 19-22 years old. Results and conclusions. 1. It has been established that the indicators of aggressiveness, charisma, energy and self-regulation are decisive in the characteristics of high-level gaming athletes. These conditions are significant in the dynamics of the growth of their sports skills. 2. It was revealed that among qualified biathletes, their psychophysiological state is dominated by indicators of balance and self-regulation with subordination of the parameters of inhibition and neuroticism. The growth of professional skills of biathletes is accompanied by directional dynamics of the indicated indicators of psychophysiological state.